Environmental risk and the precautionary principle. "Late lessons from early warnings" applied to genetically modified plants - Iulie Aslaksen; Bent Natvig; Inger Nordal (Statistics Norway, Research Department, 2004)
The environmental risk associated with genetically modified organisms (GMO) implies that new approaches to risk assessment, risk management and risk communication are needed. In this paper we discuss the role of the precautionary principle in policy responses to GMO risk. We first discuss application of the criteria in the European Environment Agency report "Late lessons from early warnings: The precautionary principle 1896-2000" to environmental GMO risk, with focus on crop plants. Moreover, we discuss Bayesian analysis in the context of improving the informational basis for decision making under uncertainty. Finally, environmental uncertainties are intertwined with economic uncertainties. Providing incentives for improved risk assessment, risk management and risk communication is crucial for enhancing social and environmental responsibility and thereby facilitate implementation of precautionary approaches. We discuss ethical screening of companies as an example of how such incentives can be provided.
Keywords: D81; Q20; Q50; 330; Environmental risk; precautionary principle; Bayesian analysis; genetically modified organisms.